Phenolic compound profiles in Finnish apple (Malus × domestica Borkh.) juices and ciders fermented with Saccharomyces cerevisiae and Schizosaccharomyces pombe strains - He, Wenjia; Laaksonen, Oskar; Tian, Ye; Heinonen, Maarit; Bitz, Lidija; Yang, Baoru (Applied Science Publishers., 2022)
The phenolic compounds in juices and ciders made with Saccharomyces cerevisiae or Schizosaccharomyces pombe from eleven Finnish apple cultivars were analyzed using liquid chromatographic and mass spectrometric methods combined with multivariate data analysis. In general, the ciders contained less phenolic compounds than corresponding apple juices. In the studied apple juices and ciders, hydroxycinnamic acids were the most predominant, accounting for around 80% of total phenolic compounds. Apple juices contained more flavonol glycosides and dihydrochalcones whereas cider processing resulted in increased amount of free hydroxycinnamic acids. The contents of individual phenolic compounds were more dependent on the apple cultivars than the yeast species. Certain cultivars contained remarkably higher contents of dihydrochalcones and hydroxycinnamic acids when comparing with other cultivars. Ciders made using S. pombe remained higher contents of procyanidins and (+)-catechin while S. cerevisiae ciders contained higher individual hydroxycinnamic acids, such as 5-O-caffeoylquinic acid, 4-O-caffeoylquinic acid, 3-O-p-coumaroylquinic acid, and 4-O-p-coumaroylquinic acid.
Keywords: Local apple cultivars; Phenolic compaunds; Juice; cider (alcoholic beverages); Finland; Yeast fermentation